Cremated Human and Animal Remains of the Roman Period : Microscopic Method of Analysis (Šepkovčica, Croatia) - Hincak, Zdravka (Array, 2007)
Human and animal cremated osteological remains from twelve graves of Roman Period from archaeological site Šepkovčica near Velika Gorica (Turopolje region, NW Croatia) were analysed. Beside the content of urns and grave pits, fillings of grave vessels like bowls, pots and amphoras from twentytwo grave samples were included in this study. The preservation of osteological and dental remains of human and animal origin was very poor, majority of fragments hardly reach lengths of 10 mm. Weight of each specimen barely exceeds 100 g per person. Apart from traditional macroscopic methods of analysing cremated remains, microscopic method for determination of age at death was also tested. Fragments of femoral bone diaphysis of eighteen persons whose remains had been found on the site were analysed. Person’ s age at death was presented in the range of five or ten years, and the long bone fragments of a child (infants) were detected. Taxonomic position for each analysed specimen was determined by microscopic analysis of animal cremated bones. Analysis results confirm validity of microscopic method in determination of age at death for human remains and taxonomic qualification of cremated animal remains from archaeological sites